From egg to maturity: a closed system for complete life cycle studies of the holopelagic jellyfish Pelagia noctiluca. (16th November 2017) - Ramondenc, Simon; Ferrieux, Mathilde; Collet, Sophie; Benedetti, Fabio; Guidi, Lionel; Lombard, Fabien
Abstract: Despite its wide spatial distribution and its high abundance in the Mediterranean Sea, the biology and the ecology of the scyphozoan species Pelagia noctiluca remain poorly understood. This is mainly due to difficulties related to sampling and its maintenance in laboratory conditions. Thus, only a few studies exist on the ecophysiology of this jellyfish species under laboratory conditions. As an example, the maximum sizes of individuals obtained in previous culturing systems were not comparable to the ones found in the environment and the authors could not obtain a second generation. Here we present an improved rearing system for P. noctiluca employing a new enclosed system running with artificial seawater. The monitoring of the jellyfish in this new system highlights the importance of the quality of the food sources provided to the cultures, as well as the volume available for jellyfish growth. We obtain adults similar in size to the ones found in the open ocean (>11 cm), and we were able to obtain a second generation, 140 days after the first one. Our system is both less time-consuming and less stressful for the jellyfish.